2011
DOI: 10.1007/978-3-7091-0693-8_14
|View full text |Cite
|
Sign up to set email alerts
|

Brain Arteriovenous Malformation Pathogenesis: A Response-to-Injury Paradigm

Abstract: Brain arteriovenous malformations (AVMs) are a rare but important cause of intracranial hemorrhage (ICH) in young adults. In this paper, we review both human and animal studies of brain AVM, focusing on the: (1) natural history of AVM hemorrhage; (2) genetic and expression studies of AVM susceptibility and hemorrhage; and (3) strategies for development of a brain AVM model in adult mice. These data target various mechanisms which must act in concert to regulate normal angiogenic response to injury. Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
86
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(94 citation statements)
references
References 64 publications
(78 reference statements)
2
86
0
3
Order By: Relevance
“…The congenital nature of brain AVMs has been previously questioned by others, 20,21,27 and as we have discussed, there is compelling evidence suggesting the postnatal development of many of these lesions. However, the exact mechanism of AVM formation has yet to be elucidated, and it may involve an interaction between genetic susceptibility and environmental (acquired) factors.…”
Section: Putative Mechanisms Of Avm Formationmentioning
confidence: 60%
See 2 more Smart Citations
“…The congenital nature of brain AVMs has been previously questioned by others, 20,21,27 and as we have discussed, there is compelling evidence suggesting the postnatal development of many of these lesions. However, the exact mechanism of AVM formation has yet to be elucidated, and it may involve an interaction between genetic susceptibility and environmental (acquired) factors.…”
Section: Putative Mechanisms Of Avm Formationmentioning
confidence: 60%
“…35 In addition, a variety of candidate gene studies in patients with sporadic AVMs have identified single-nucleotide polymorphisms (SNPs) associated with a susceptibility to develop AVMs and with their progression to intracerebral hemorrhage. 20,34 Most of the studied genes code for essential proteins in the angiogenic and inflammatory cascades. A recent systematic review included all the studies reporting SNPs associated with sporadic brain AVMs, and after a joint analysis of the risk estimates described in the different reports, a statistically significant association was found between an SNP in the ALK1 gene (intervening sequence 3-35A>G) and a susceptibility to develop a brain AVM (OR 2.19, 95% CI 1.25-3.83).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of SRS, embolization, and microsurgery may be used in the palliative management of Spetzler-Ponce Class C lesions. 15,22,36,41 Given that the large majority of high-grade lesions cannot be treated without relatively high morbidity and mortality using current surgical and radiosurgical paradigms, new cellular and molecular biological therapies are under development aiming toward radiosensitization, vascular targeting, and remodeling therapies. 27,43 The current AVM treatment paradigm does not take into consideration any special factors related to the genetics or molecular constitution of the specific patient who has an AVM.…”
Section: Current Managementmentioning
confidence: 99%
“…AVMs are dynamic lesions that show evidence of active angiogenesis, inflammatory responses, and adaptive structural changes to its components over time. 31 AV shunting results in feeding artery dilatation and draining vein arterialization. 9,30 Histologically, the arterial elastic and muscular layers are altered.…”
Section: Pathophysiologymentioning
confidence: 99%